STUDI PERANCANGAN PRODUKSI PAPAN BUBUTMEN - Antriksa, K; Salain, I M. Alit K; Wiryasa, N. M. Anom (JURNAL SPEKTRAN; Vol 4 No 1 (2016): Vol. 4, No. 1, Januari 2016, 2016)
Abstract : Research on the design study of the "Bubutmen" board production (bamboo, coir fiber and cement), serves as a separator material in buildings. The objective of design includes architecture function and financial feasibility. Architecture functions include water absorption, shape, size, and weight of the "Bubutmen” board. Financial feasibility includes selling price, profit, production quantity at the breakeven point and the availability of raw materials. Availability of raw materials is calculated based on statistical data until 2016. Mechanical functions include the maximum load on the license "Bubutmen" board than Yumen board. The design aspects of water absorption and weight "Bubutmmen" board carried through hollow bamboo frame design and mix plastering with cement weight ratio, coir fiber and water is 5: 1: 3.167. The design aspects of the shape and size of the print is done through a planning tool. The design is done through the financial aspects of fuel efficiency and effectiveness of the production process.The design of the technical aspects of planning through the hollow bamboo frame, designed two variants namely "model 1" consists of 12 pieces of bamboo rods long, "Model 2" consists of 7 pieces of a long bamboo rods. The results of the design "Bubutmen" board "Model 1" acquired 24 585% water absorption and "Model 2" 15.135%. The form of a board with a length of 2400 mm, width 600 mm and 30 mm thick. Heavy "Bubutmen" board "Model 1" of 38.250 kg and "Model 2" amounting to 43.486 kg. Availability of raw materials until 2016 are eligible needs so worthy produced. The results of the financial feasibility "Model 1" full production system with a selling price of Rp 115,806.17 / unit, profit Rp 17,546.39 and the amount of production at the breakeven point 75 units. "Model 2" full production system with a selling price of Rp 113,486.14 / unit, profit Rp 17,194.87 and the amount of production at the breakeven point 76 units. "Model 1" production system of semi-finished materials with the selling price of Rp 113,628.17 / unit, profit Rp 17,216.39 and the amount of production at the breakeven point 76 units. "Model 2" production system of semi-finished materials and selling price Rp111.638,14 / unit, profit Rp 16914.87 and the amount of production at the breakeven point 77 production units. The results of the maximum load on the deflection permit Yumen board is 51.07 kg, "Model 1" 32.72 kg and "Model 2" 55.94 kg.
Keywords: Bubutmen, bamboo, fiber, cement and water